Imobilização e estabilização de D-Hidantoinase para a produção de N-Carbamoil-D-Fenilglicina - Becaro, Aline Aparecida (2008)
Immobilization and stabilization of enzymes increases their potential for use in industrial scale. D-hydantoinases (dihidropirimidina amidrohidrolase EC 3.5.2.2) catalyze the hydrolysis of D-hydantoins, generating the corresponding Ncarbamoil- D-amino acid and are used in the production of D-amino acids, including Dphenylglycine and D-p-hydroxyphenylglycine.This work reports studies for immobilization and stabilization of D-hydantoinase from Vigna angularis (E.C. 3.5.2.2.). Different strategies of multipoint covalent attachment in organic supports as chitosan and agarose were used. Different protocols of immobilization were employed, being the adittion of ions during the reduction step with the NaBH4 important to protect enzyme catalytic site. The active and stabilized derivatives were used to catalyze the hydrolysis of D-phenylhydantoin. The temperature and pH enzyme profiles showed maximum enzyme activity at 60ºC and pH 10,0. The subunits of the enzyme present molecular mass aroundt 50kDa. The enzyme immobilized in glyoxyl-agarose in the presence of Zn2+ ions during the reduction step, with immobilization time of 24h, was the best derivative, being 89-fold more stable than the soluble enzyme. The analysis of amino acids showed that a 50% of lysines residue present in the enzymes was covalently linked in glyoxyl-agarose. The enzyme immobilized in epoxy-chitosan-alginate was 20-fold more stable than the soluble enzyme. All the tested immobilization protocols led to 100% of immobilization yield. Soluble enzyme and the best glyoxyl and chitosan enzyme derivatives were used to catalyze the hydrolysis of D- phenylhydantoin , and led to the production of 99% of NCarbamoil- D-Phenylglycine after 3, 9 and 15h of reaction respectively.